A study of the chemical and microbial changes in whole-plant corn silage during exposure to air: effects of a biological additive and sealing technique - Uriarte-Archundia, M.E.; Bolsen, K.K.; Brent, B.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The objectives of this study with whole-plant corn silage were to determine the effects of a biological additive and sealing technique on yeast and mold populations; and to examine the relationship between the microbial and chemical changes in the silages during exposure to air. Whole-plant corn was harvested at 80% milkline (36% DM), and ensiled at a density of 35 lb of fresh matter/ft3. Half of the pre-ensiled forage was treated with a biological additive (A) (Sil-All 4×4, Alltech, Inc.); the other half of the pre-ensiled forage was the untreated control (C). Half of the silos in the A and C groups were sealed immediately after filling (S=sealed) and the other half of the silos were sealed 48 hours after filling (DS=delayed seal). Treatments consisted of combinations of the two factors: additive (A and C) and sealing technique (S and DS). There were three, 5-gal capacity, laboratory silos per treatment. Silos were opened after 150 days, and the chemical and microbial compositions and aerobic stability of the silages determined. All four silages were moderately stable during exposure to air. The C, DS silage was the first to show a rise in temperature, which occurred after 65 hours. The two DS silages were 48 hours less stable than their S counterparts, and the two A silages were 24 hours more stable than their C counterparts. Deterioration of the silages during exposure to air was accompanied by an increase in temperature and pH, a decrease in lactic acid content, and a rapid increase in the lactate-assimilating yeast population. Treatment with a biological additive significantly improved aerobic stability, and delayed sealing reduced the aerobic stability of silages.
Keywords: Beef; Corn silage; Inoculant; Aerobic deterioration; Sealing